Forming of the economy based on knowledge. (Journal of Economic Research & Business Administration, 2015)
The growing importance of knowledge in the scientific and technical progress acts as a driving force for further economic development of the economy of Kazakhstan. Kazakhstan’s economy raises the problem of increasing the competitiveness of domestic enterprises on the basis of the transition to an innovation economy.
Keywords: scientific and technological progress; innovation economy; innovation potential; modernization; innovation business; human capital